Cloning, Expression and Purification of Subunit H of Vacuolar H(+)-ATPase from Mythimna separata Walker (Lepidoptera: Noctuidae) - Lu, Lina (MDPI, 2014)
The vacuolar (H(+))-ATPase (V-ATPase) of insect, which is composed of membrane-bound V(0) complex and peripheral V(1) complex, participates in lots of important physiological process. Subunit H, as a subunit of V(1) complex, plays a vital role in bridging the communication between V(1) and V(0) complexes and interaction with other proteins. Yeast subunit H has been successfully crystallized through expression in E. coli, but little is known about the structure of insect subunit H. In this study, we cloned, expressed and purified the subunit H from midgut of Mythimna separata Walker. Through RACE (rapidly amplification of cDNA ends) technique, we got 1807 bp full length of subunit H, and to keep the nature structure of subunit H, we constructed Baculovirus expression vector with His-tag in the C-terminal and expressed the recombinant protein in insect sf9 cells, thereafter, purified the recombinant protein by Ni-NTA columns. Results of SDS-PAGE, western blotting and mass spectrometry showed that the recombinant protein was successfully expressed. The method of expressing and purifying M. separata subunit H will provide a foundation for obtaining the crystal of subunit H and further study of the design of novel insecticides based on its structure and function.